Complete genome sequence of Desulfotomaculum acetoxidans type strain (5575(T)) - Spring, Stefan (Michigan State University, 2009)
Desulfotomaculum acetoxidans Widdel and Pfennig 1977 was one of the first sulfate-reducing bacteria known to grow with acetate as sole energy and carbon source. It is able to oxidize substrates completely to carbon dioxide with sulfate as the electron acceptor, which is reduced to hydrogen sulfide. All available data about this species are based on strain 5575(T), isolated from piggery waste in Germany. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first completed genome sequence of a Desulfotomaculum species with validly published name. The 4,545,624 bp long single replicon genome with its 4370 protein-coding and 100 RNA genes is a part of the Genomic Encyclopedia of Bacteria and Archaea project.